On Micro Continuous Function via ?g ?? -closed Set - V.Thiripurasundari, R.Vijayalakshmi (Mathematical Statistician and Engineering Applications, 2023)
Recently we introduced -closed set in Micro topological spaces. The aim of this paper is to introduce a new class of Micro continuous function called -continuous function in Micro topological spaces and also discussedtheir properties.